2013
DOI: 10.1061/(asce)gt.1943-5606.0000884
|View full text |Cite
|
Sign up to set email alerts
|

Pile Aging in Cohesive Soils

Abstract: Abstract:This technical note presents the results of a field investigation into pile aging in soft clay which was conducted over a period of ten years. Static load tests were conducted after the excess pore pressure generated by the installation of 6 m long driven concrete piles were fully equalised. These tests allowed the time-capacity aging profile to be established. A normalised capacity-time trend established for the case history is seen to be consistent with the response observed from a wider database of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…where s = āˆš š¬ āˆ¶ š¬āˆ•2 is the square root of the second invariant of the deviatoric stress tensor; š‘£ š‘§ is the excess volume per STZ; and š‘  0 is the initial yield stress. It is noted that the exponential term in Equation (5) suggests that STZs transition faster with higher stress ratio sāˆ•š‘ but lower compactivity šœ’. It is seen from Equation (4) that increasing šœ’ has a competing effect on the plastic strain rate as the STZ density increases but the STZ transition rate decreases.…”
Section: Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…where s = āˆš š¬ āˆ¶ š¬āˆ•2 is the square root of the second invariant of the deviatoric stress tensor; š‘£ š‘§ is the excess volume per STZ; and š‘  0 is the initial yield stress. It is noted that the exponential term in Equation (5) suggests that STZs transition faster with higher stress ratio sāˆ•š‘ but lower compactivity šœ’. It is seen from Equation (4) that increasing šœ’ has a competing effect on the plastic strain rate as the STZ density increases but the STZ transition rate decreases.…”
Section: Plasticitymentioning
confidence: 99%
“…1,2 They play critical roles in foundation engineering, such as the long-term settlement of superstructures built on clay 3 and the setup of piles installed in clay. 4,5 Reliable modelling of the time-dependent behaviours of clay under complex loading conditions is of great significance but remains challenging due to the lack of a unified, robust yet handy theoretical framework to describe these time-dependent characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Postconsolidation gains in shaft capacity are referred to as aging (e.g., Doherty and Gavin 2013). Eq.…”
Section: Optimization Analysesmentioning
confidence: 99%
“…They indicated that new findings with the piles could be employed to characterize more clearly the strong aging effects. Dohersty and Gavin (2013) made a field investigation in concrete pile aging in soft clay that was conducted over a period of 10 years. A simple reliability-based design example was presented to highlight the positive pile aging effect by showing the increasing reliability indices calculated from the measured pile capabilities at different time after pile installation.…”
mentioning
confidence: 99%